2012
DOI: 10.1159/000342814
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Lipid Profile and Atherogenic Risk during Androgen Deprivation Therapy in Prostate Cancer Patients

Abstract: Objective: To analyse changes in lipid profiles observed in patients receiving androgen deprivation therapy (ADT) and to evaluate differences between medical castration and maximal androgen blockade (MAB). Material and Methods: Serum levels of total cholesterol (TC), high-density lipoproteins (HDL), low-density lipoproteins (LDL) and triglycerides (TG) were prospectively evaluated in 33 patients with locally advanced or metastatic prostate cancer treated with ADT. The median age was 73.4 years. Serum lipids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 33 publications
5
22
1
Order By: Relevance
“…Thus, there may be residual confounding affecting the analysis of those on anti-androgen monotherapy. Alterations in lipid levels may be another mechanism through which systemic ADT is propagating risk of TED [26][27][28][29][30]. Our dataset does not contain information on any of these factors and thus further mechanistic studies are required to determine if these do play a role in the associations observed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be residual confounding affecting the analysis of those on anti-androgen monotherapy. Alterations in lipid levels may be another mechanism through which systemic ADT is propagating risk of TED [26][27][28][29][30]. Our dataset does not contain information on any of these factors and thus further mechanistic studies are required to determine if these do play a role in the associations observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in cardiovascular morbidity observed in patients receiving ADT cannot be explained by the changes observed in the lipid profile [46]. Moreover, before starting ADT, it could be interesting to investigate PCa physiopathology along the pituitary-testis-prostate axis.…”
Section: Discussionmentioning
confidence: 99%
“…As well as weight gain, several studies showed a mean increase of 3.2–10.6% in total cholesterol and 3.8–46.6% in triglycerides, with the duration of ADT ranging from 24 weeks to 12 months (Table ) . These changes in lipid and glucose levels were noticeable in the first 3 or 6 months of ADT (Figs ) . Only one study compared the differences in lipid profile according to treatment modality .…”
Section: Metabolic Changes During Adtmentioning
confidence: 99%